The Impact of Gratitude on Academic Flow among Students at MAN 2 Hulu Sungai Tengah - Rahmilawati, Rahmilawati (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This study explores the influence of gratitude on students' academic flow at MAN 2 Hulu Sungai Tengah. Academic flow, defined as a state of total immersion and enjoyment in tasks, is essential for students’ engagement and concentration. However, many students struggle to achieve this state consistently. Gratitude, a key aspect in positive psychology, is believed to enhance emotional stability, which can support academic flow. Employing a quantitative method with survey and questionnaire tools, this study sampled 70 students aged 15 to 18. Data were analyzed using descriptive statistics and simple linear regression. Findings reveal a significant positive relationship between gratitude and academic flow, with gratitude accounting for 66.4% of the variance in academic flow (R² = 0.664). These results highlight that gratitude may foster a positive emotional state conducive to focused learning. This research offers insights for Islamic education, suggesting that cultivating gratitude in students can potentially enhance their academic experiences and outcomes.